The regulation of Ero1-alpha in homocysteine-induced macrophage apoptosis and vulnerable plaque formation in atherosclerosis. (October 2021) - Zhang, Na; Zhu, Lili; Wu, Xianxian; Yan, Ru; Yang, Shaobing; Jiang, Xiaoliang; Liu, Xing; Liu, Xue; Yan, Ning; Cong, Guangzhi; Yang, Zhiwei; Jia, Shaobin
Abstract: Background and aims: Hyperhomocysteinemia (HHcy) is an independent risk factor for atherosclerosis and plaque vulnerability. Macrophage apoptosis mediated by endoplasmic reticulum (ER) stress plays an important role in the pathogenesis of HHcy-aggravated atherosclerosis. Endoplasmic reticulum oxidoreductase 1α (Ero1α) is critical for ER stress-induced apoptosis. We hypothesized that Ero1α may contribute to ER-stress induced macrophage apoptosis and plaque stability in advanced atherosclerotic lesions by HHcy. Methods: Apoe −/− mice were maintained on drinking water containing homocysteine (Hcy, 1.8 g/L) to establish HHcy atherosclerotic models. The role of Ero1α in atherosclerotic plaque stability, macrophage apoptosis and ER stress were monitored in the plaque of aortic roots in HHcy Apoe −/− mice with or without silence or overexpression of Ero1α through lentivirus. Mouse peritoneal macrophages were used to confirm the regulation of Ero1α on ER stress dependent apoptosis in the presence of HHcy. Results: Atherosclerotic plaque vulnerability and macrophage apoptosis were promoted in Apoe −/− mice by high Hcy diet, accompanied by the upregulation of Ero1α expression and ER stress. Inhibition of Ero1α prevented macrophage apoptosis and atherosclerotic plaque vulnerability, and vice versa . Consistently, in mouse peritoneal macrophages, ER stress and apoptosis were attenuated by Ero1α deficiency, but enhanced by Ero1α overexpression. Conclusions: Hcy, via upregulation of Ero1α expression, activates ER stress-dependent macrophage apoptosis to promote vulnerable plaque formation in atherosclerosis. Ero1α may be a potential therapeutic target for atherosclerosis induced by Hcy. Graphical abstract: Image 1 Highlights: Homocysteine (Hcy) exacerbates atherosclerotic plaque vulnerability, macrophage apoptosis, and ER stress with upregulation of Ero1α. Ero1α mediates the development of vulnerable plaque formation induced by Hcy. Ero1α contributes to the development of Hcy-accelerated plaque by inducing apoptosis and stimulating endoplasmic reticulum stress in macrophages.